-2(t-7)-(t-5)=5

Simple and best practice solution for -2(t-7)-(t-5)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(t-7)-(t-5)=5 equation:


Simplifying
-2(t + -7) + -1(t + -5) = 5

Reorder the terms:
-2(-7 + t) + -1(t + -5) = 5
(-7 * -2 + t * -2) + -1(t + -5) = 5
(14 + -2t) + -1(t + -5) = 5

Reorder the terms:
14 + -2t + -1(-5 + t) = 5
14 + -2t + (-5 * -1 + t * -1) = 5
14 + -2t + (5 + -1t) = 5

Reorder the terms:
14 + 5 + -2t + -1t = 5

Combine like terms: 14 + 5 = 19
19 + -2t + -1t = 5

Combine like terms: -2t + -1t = -3t
19 + -3t = 5

Solving
19 + -3t = 5

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-19' to each side of the equation.
19 + -19 + -3t = 5 + -19

Combine like terms: 19 + -19 = 0
0 + -3t = 5 + -19
-3t = 5 + -19

Combine like terms: 5 + -19 = -14
-3t = -14

Divide each side by '-3'.
t = 4.666666667

Simplifying
t = 4.666666667

See similar equations:

| 1.6=7-5(k+1.1) | | 9x-5x-19=21-10 | | 16=7(4)+v | | m/-8-5m-2 | | x/4-7=25 | | 4(x-5)-8=-3 | | 6.8x-4.7=17.63 | | 9x+3y=63forx | | -1(15)+195= | | x+7/2-7=2x-5/3 | | 2g+23=-55 | | 2y^2=-9y+5 | | -18-6(-1)=6(1)+3(-1) | | 2(15)+150= | | p=2(9)+2w | | 13w+1=5w-6 | | -10/6=(3p+1)/(p+6) | | 2/8n+6=10 | | x^3-3.1x^2-27.74x+17.544=0 | | -1/3z+4.6=21.6 | | .37-1.82= | | 2(4x-3)=-6 | | 2/8n | | 8x=31-y | | 3/(3k-6)=7/(k+2) | | 2xm=5 | | -4(9+3x)=-120 | | x+7=0.5 | | 4(4-4d)=-10-16d | | w/3-16=-8 | | 5-3/8k=20 | | -4/5x+1=-8/5+7x |

Equations solver categories